Grass-dependent Thysanoptera of the family Thripidae from Australia - Mound, Laurence A. (Zootaxa, 2011)
The diversity of Thysanoptera associated with grasses worldwide is discussed. Associations between thrips and members of the Poaceae have evolved independently in three thrips families. In Australia, almost 70 species of Thripidae are recorded as specific to Poaceae. Most of these thrips breed only on leaves, with 10 species in four genera breeding in grass florets, and a very few species feeding on both leaf and flower tissues. An identification key is provided to 28 genera of Thripidae found in Australia and known to be fully dependent on Poaceae, including four new genera of Thripinae with 16 new species. The new taxa are: Aliceathrips gen.n., A. mnestes sp.n., A. engaius sp.n., A. palmeri sp.n., A. sorghi sp.n. Bregmatothrips australis sp.n. Kranzithrips mareebai gen. & sp.n. Masamithrips gen.n., M. masamii sp.n., M. geikiei sp.n., M. melinus sp.n., M. tanyoeikus sp.n., M. williei sp.n., M. wyndhami sp.n. Monothrips cuspis sp.n. Parexothrips palumai sp.n. Stenchaetothrips bambusicola sp.n. Striathrips sulcatus gen. & sp.n. One nomenclatural change is Aliceathrips australiensis (Girault) comb.n. transferred from Bolacothrips. The following five species are newly recorded from Australia: Bolacothrips striatopennatus (Schmutz), Bregmatothrips binervis (Kobus) [with Bregmatothrips saccharicolus (Bianchi) as a new synonym], Exothrips sacchari (Moulton), Stenchaetothrips indicus (Ramakrishna & Margabandhu) [with Stenchaetothrips brasiliensis(Hood) as a new synonym], Takethrips megas Nonaka & Jangvitaya.